Handbook of fiber optic data communication (Academic Press, 1998)
The book offers an overview of data communication using both fiber optics and optoelectronics. Its also offers guidance all the industry standards, gives a complete list of sites on the Internet and World Wide Web for more data online, and interprets professional opportunities in fiber optics